The role of 4-nitrobenzoic acid polymorphs in the crystallization process of organic acid-base multicomponent systems - Croitor, Lilia; Petric, Mihaela F.; Szerb, Elisabeta, I; Vlase, Gabriela; Bourosh, Paulina N.; Chumakov, Yurii M.; Crisan, Manuela E. (Royal Soc Chemistry, 2019)
The role of polymorphs in understanding and controlling the crystallization process from solution of an organic acid-base system is reported. Herein, the crystallization process of dimethylethanolammonium 4-nitrobenzoate (DMEA4NB) is explored through different pathways of crystallization, using 4-nitrobenzoic acid polymorphs crystallized in different space groups: monoclinic P2(1)/n (4NBH) and C2/c (4NBH*), respectively. The crystal growth process was investigated by complementary experimental techniques such as single crystal and powder X-ray diffraction, Fourier transform infrared spectroscopy, hot-stage optical microscopy and thermogravimetric analysis correlated with an ab initio computational study. The experimental and theoretical data revealed that 4NBH is more stable than 4NBH*, indicating that 4NBH* is more favorable for a one-step crystal growth process, while the 4NBH polymorph leads to DMEA4NB formation through three intermediate phases. The changes over time associated with solid-solid phase transformations in the crystal growth process are evaluated. The opacification process of DMEA4NB has indicated the partially reversible transformation of the product into an intermediate phase.
Keywords: Adapted Perturbation-Theory; Crystal-Structure; Monoethanolamine Salts; Carboxylic-Acids; Benzoic-Acids; Refinement; Network